(untitled) (Itinera, 2025)
Techniques of Disinterestedness. Aesthetic Pleasure and Purpose-Oriented Actions from Kant to Simondon Kantian aesthetics has often been read as attempting to ground on disinterested pleasure the difference between aesthetic experience of the work of art and purpose-oriented action, which can at best be combined with interested pleasure. Both George Dickie and Thomas Hilgers, though from different readings, agree that disinterestedness excludes practical activity. I intend to show that an aesthetics that takes its cue from Kant can consider examples of practical activity as cases in which disinterested pleasure occurs. This happens in cases in which experience is linked to the interest of human beings in finding agreement between nature and freedom. The fact that Kant uses technique as an example to explain some features of aesthetic judgment shows that the Kantian difference between technique and art is less clear-cut than it might appear. On the basis of the relationship between technique and art, it is possible to reflect on cases in which aesthetic pleasure is not pure and thus a relationship between interest and disinterest is allowed. I will highlight that Gilbert Simondon’s techno-aesthetics further deepens the link between interest and disinterest. This link appears in an exemplary way when the technical operation is accompanied by a pleasure that cannot be reduced to the simple mechanism of impressions but requires a rethinking of aesthetics as reflections on the conditions of possibility of our operation.